2010
DOI: 10.1590/s0044-59672010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Conforto ambiental de bezerros bubalinos (Bubalus bubalis Linnaeus, 1758) em sistemas silvipastoris na Amazônia Oriental

Abstract: Foi analisado o efeito de dois sistemas silvipastoris nos índices de conforto ambiental e alterações nos parâmetros fisiológicos de bezerros bubalinos criados na Embrapa Amazônia Oriental, Belém-PA (clima Afi), no Período 1 (abril a setembro/2007) e Período 2 (outubro/2007 a março/2008). Foram inseridos onze bezerros no Sistema Silvipastoril 1 (SSP1), que apresentava sombreamento útil nas pastagens de 18 a 21%, e oito no Sistema Silvipastoril 2 (SSP2), sem sombreamento, com lago para banho. Foram mensuradas as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 4 publications
1
9
1
1
Order By: Relevance
“…These results show how important silvopastoral systems are in buffalo farming in hot, high-humidity regions such as the Amazon, since it is known that air temperature under tree canopies can be 2 to 3 °C below that under full sunlight due to the positive interference of leaves in the passage of solar radiation (Moraes Júnior et al, 2010). AT -air temperature; RH -relative humidity; GTHI -index of globe temperature and humidity.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…These results show how important silvopastoral systems are in buffalo farming in hot, high-humidity regions such as the Amazon, since it is known that air temperature under tree canopies can be 2 to 3 °C below that under full sunlight due to the positive interference of leaves in the passage of solar radiation (Moraes Júnior et al, 2010). AT -air temperature; RH -relative humidity; GTHI -index of globe temperature and humidity.…”
Section: Resultsmentioning
confidence: 68%
“…This result emphasises the importance of using trees in management systems to provide greater thermal comfort for animals (Moraes Júnior et al, 2010;Silva et al, 2011) and improve their yield (Castro et al, 2008;Moraes Júnior et al, 2010;Garcia et al, 2011). Incorporating trees into pastures in hot, humid climate regions favors the microclimate and provides better thermal comfort conditions, since shading can lower GTHI compared with areas under full sunlight (Garcia, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings in the current study did not indicate a thermal stress situation. Likewise, previous research conducted in the Afi type climate demonstrated that buffalo did not present heat stress or reduction of growth performance when THI was between 73.5 and 82.2 (Moraes Júnior et al, 2010) or when THI varied from 75.0 to 81.0 . Regarding ICB, the values found in the present study were similar to those reported by for adult buffalo (1.7 to 2.4).…”
Section: Discussionmentioning
confidence: 65%
“…The buffalo is a homeothermic animal, but when submitted to elevated temperatures and relative humidity may undergo heat stress (Moraes Júnior et al, 2010). However, around 85% of domestic buffaloes are raised in the intertropical zone, which predisposes these animals to a situation of permanent thermal challenge (Garcia, 2013).…”
Section: Introductionmentioning
confidence: 99%